Quality Evaluation of Ayurvedic Crude Drug Daruharidra, Its Allied Species, and Commercial Samples from Herbal Drug Markets of India - Srivastava, Sharad (Hindawi Publishing Corporation, 2013)
Berberis aristata known as “Daruharidra” in Ayurveda is a versatile medicinal plant used singly or in combination with other medicinal plants for treating a variety of ailments like jaundice, enlargement of spleen, leprosy, rheumatism, fever, morning/evening sickness, snakebite, and so forth. A major bioactive marker of this genus is an alkaloid berberine, which is known for its activity against cholera, acute diarrhea, amoebiasis, and latent malaria and for the treatment of oriental sore caused by Leishmania tropica. Although the roots of B. aristata are considered as the official drug (Ayurvedic Pharmacopoeia of India), the study revealed that different species of Berberis, namely. B. asiatica, B. chitria, and B. lycium are also used under the name of Daruharidra in different parts of the country. Detailed physicochemical and phytochemical studies of subjects like total ash, acid insoluble ash, tannins, and total alkaloids were calculated from the shade dried powdered material according to the recommended procedures. Further, heavy metal studies and quantitative estimation of berberine through HPTLC have also been performed as per ICH guidelines. A detailed study of four Berberis species, namely B. aristata, B. asiatica, B. chitria, and B. lycium, which are implicated as Daruharidra and collected from wild and ten commercial samples procured from various important drug markets in India has been carried out, which may be useful to pharmaceutical industries for the authentication of the commercial samples and exploring the possibilities of using other species as a substitute of B. aristata.